2002
DOI: 10.1002/cjoc.20020201142
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Synthesis and Antitumor Activity of Phosphorylated Achyranthes bidentata Polysaccharide (P‐AbPS)

Abstract: Ihe synthesis of phosphorylated AchynmUres bidentota pdysaccbaride (P-AbPS) wss reported based on Merent strategies.obtained when phosphorus oxycbloride (PO(&) was used as a phosphorylating agent and trimethyl phosphate-pyridine or dimethyl formamide wss used as solvent. The hhences of different solvents and d o n conditions were discussed . The pharmmlogv assay shorn that P-AhPS postses antitumor activity against sarcoma 180 and Lewis lung cancer in mice. The P-AbFS With l&h d m of s u b s t i w o n (D.S. > 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It has been reported that phosphated polysaccharides exhibited anti-inflammatory, anti-tumor or anti-viral activities, especially immunomodulatory (Chen, Zhang, & Tian, 2002;Lyuksutova et al, 2005;Williams et al, 2004). Specifically, the phosphorylated Achyranthes bidentata polysaccharide with high degree of substitution was obtained when phosphorus oxychloride was used as phosphorylating agent, and it possessed anti-tumor activities against Sarcoma 180 and Lewis lung cancer in mice (Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that phosphated polysaccharides exhibited anti-inflammatory, anti-tumor or anti-viral activities, especially immunomodulatory (Chen, Zhang, & Tian, 2002;Lyuksutova et al, 2005;Williams et al, 2004). Specifically, the phosphorylated Achyranthes bidentata polysaccharide with high degree of substitution was obtained when phosphorus oxychloride was used as phosphorylating agent, and it possessed anti-tumor activities against Sarcoma 180 and Lewis lung cancer in mice (Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, the phosphorylated Achyranthes bidentata polysaccharide with high degree of substitution was obtained when phosphorus oxychloride was used as phosphorylating agent, and it possessed anti-tumor activities against Sarcoma 180 and Lewis lung cancer in mice (Chen et al, 2002). Williams et al have successfully prepared water-soluble glucan phosphate which was derived from water-insoluble (1 → 3)-␤-d-glucan in Saccharomyces cerevisiae (Williams et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have therefore focused on converting these glucans into a water-soluble form through chemical modification such as amination [13], sulfation [14] and phosphorylation [15]. It has also been demonstrated that such modified polysaccharides exhibit anti-inflammatory, anti-tumor, anti-viral and immunomodulatory activities [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharide derivatives have antitumor activity. Phosphorylated Achyranthes bidentata polysaccharide (P-ABPS) showed antisarcoma activity in a mouse model of Lewis lung cancer (Chen et al, 2002;Huang & Huang., 2017). activity (Qi et al, 2005;Shao et al, 2013;Suzuki & Terasawa, 2020;Wei et al, 2012).…”
Section: Antitumor Activities Of Lotus Root Polysaccharide 1 and Phosphorylated Lotus Rootmentioning
confidence: 99%